Efficacy of a dentifrice for dentine hypersensitivity containing 5.6% potassium citrate and 0.3% sodium fluoride: a randomized clinical controlled trial - Ramón-Morales, Oscar Miguel; Londoño, Walter; González-Ortíz, Leydi Gisela; González-Patiño, Elizabeth; Blandón, Nadya; García, Nora (Revista Facultad de Odontología Universidad de Antioquia, 2010)
Introduction: potassium and fluoride salts have been used for the treatment of dentine hypersensitivity. The objective of this study was to determine the efficacy of a tooth paste with 5.6% of potassium citrate and 0.3% of sodium fluoride for the treatment of dentine hypersensitivity. Methods: a randomized sample of 100 people, male and female from the Valle de Aburrá, older than 18 years of age, with dentine hypersensitivity and who met the inclusion criteria was selected. A randomized triple blind clinical trial was designed, using a control group (placebo), and an experimental group (tooth paste for sensitive teeth). The subjects were given a questionnaire in which they rated the intensity of the pain using the visual analogical scale before the intervention; next, a tooth was selected in each person and subjected to a thermal stimulus test and constant pressure contact test, also rating the intensity of the pain in each test using the visual analogical pain scale. Each subject received a soft toothbrush and the product containing the active principle or the placebo was supplied to them at random. The patients were evaluated and subjected to the same tests used at the beginning of the study, at the fourth week and at the eight week, registering the data obtained for each of the tests during the three evaluation periods. None of the participants, that is, neither the doctor, nor the patient nor the statistician knew which toothpaste (active component or placebo) was supplied to the patients. Results: the results showed that there was a decrease in hypersensitivity in both groups; however, the sensitivity toothpaste showed a greater decrease in all the measurements with the different tests applied. Conclusions: although there was a decrease in the symptoms of the placebo group, there was a statistically significant larger decrease in the group that used the sensitivity toothpaste.